A Comparative Study of Particulate Matter Between New Delhi, India and Riyadh, Saudi Arabia During the COVID-19 Lockdown Period - Singh, Bhupendra Pratap; Eldesoky, Gaber E.; Kumar, Pramod; Chandra, Prakash; Islam, Md Ataul; Rahman, Shakilur (Frontiers in Environmental Science, 2022)
The impact of particulate matter during the lockdown period needs attention to correlate anthropogenic and natural emissions. Therefore, the current study demonstrated the changes in fine particulate matter PM2.5, PM10 and their effect on air quality during the lockdown. The air quality of India is influenced by raising dust and sand from the desert and surrounding areas and carrying it over a large distance. Thus, the current study becomes important in changes in the air quality of the Indian sub-continent associated with the effect of dust storms from long distances. The result indicated a significant reduction of PM2.5 and PM10 from 93.24 to 37.89 µg/m3 and 176.55 to 98.87 µg/m3 during the lockdown period as compared to pre lockdown period, respectively. The study shows that average concentrations of PM10 and PM2.5 have declined by -44% and -59% during the lockdown period in Delhi. The average value of median PM10 was calculated at 33.71µg/m3 for Riyadh, which was observed much lower than New Delhi during the same period. The values of PM10 were observed different trends for pre and during the lockdown period in Riyadh, indicating considerable influence from natural (sand and dust storms) and anthropogenic sources during the lockdown periods. This study could be scaled up nationwide and this might be helpful in the formulation of air pollution reduction policies in the future.